The anti-cancer effect of series of strained photoactivatable Ru(II) polypyridyl complexes on non-small-cell lung cancer and triple negative breast cancer cells - Fayad, Christelle (2021)
Ruthenium complexes have been recently reported as potential chemotherapeutic agents that offer tumor selectivity and low tumor resistance. This study investigates the photochemistry and the effect of four strained photoactivatable polypyridyl ruthenium(II) complexes on non-small-cell lung cancer (A549) and triple negative breast cancer (MDA-MB-231) cells. All four ruthenium(II) complexes, [Ru(bpy)2dmbpy]Cl2 (C1) where (bpy = 2,2′-bipyridine and dmbpy = 6,6′-dimethyl-2,2′-bipyridine), [Ru(phen)2dmbpy]Cl2 (C2) where (phen = 1,10-phenanthroline), [Ru(dpphen)2dmbpy]Cl2 (C3) (where dpphen = 4,7-diphenyl-1,10-phenanthroline) and [Ru(BPS)2dmbpy]Na2 (C4) where (BPS = bathophenanthroline disulfonate) eject the dmbpy ligand upon activation by blue light. Determination of the octanol–water partition coefficient (log P) revealed that C3 was the only lipophilic complex (log P = 0.42). LC–MS/MS studies showed that C3 presented the highest cellular uptake. The cytotoxic effect of the complexes was evaluated with and without blue light activation using WST-1 kit. Data indicated that C3 exhibited the highest cytotoxicity after 72 h (MDA-MB-231, IC50 = 0.73 µM; A549, IC50 = 1.26 µM) of treatment. The phototoxicity indices of C3 were 6.56 and 4.64 for MDA-MB-230 and A549, respectively. Upon light activation, C3 caused significant ROS production and induced apoptosis in MDA-MB-231 cells as shown by flow cytometry. It also significantly increased Bax/Bcl2 ratio and PERK levels without affecting caspase-3 expression. C3 exhibited poor dark toxicity (IC50 = 74 μM) on rat mesenchymal stem cells (MSCs). In conclusion, the physical property of the complexes dictated by the variable ancillary ligands influenced cellular uptake and cytotoxicity. C3 may be considered a promising selective photoactivatable chemotherapeutic agent that induces ROS production and apoptosis.